Formulasi dan Karakterisasi Fisik Sediaan Emulgel Facial wash dengan Menggunakan Kombinasi Minyak Almond (Prunus amygdalus dulcis) dan Surfaktan Sodium Lauryl Sulfate - Paneo, Mohamad Aprianto; Thomas , Nur Ain; Latif, Multiani S; Tuloli, Teti Sutriyati; Nurkamiden, Sri Devi Maharani (Journal of Pharmaceutical and Sciences, 2025)
Background: Prunus amygdalus dulcis (almond) is a plant whose seeds produce oil with significant benefits for skin health. Almond oil contains essential compounds, such as oleic acid and other bioactive substances, which possess anti-inflammatory and moisturizing properties, making it a potential ingredient in cosmetic pharmaceutical formulations. Objective: This study aimed to formulate a facial wash containing almond oil and to evaluate its physical and organoleptic characteristics in combination with Sodium Lauryl Sulfate (SLS) as a surfactant. Methods: Three emulgel formulations were developed with varying concentrations of almond oil (10%, 15%, 20%) and SLS (1%, 1.5%, 2%). Evaluations included organoleptic tests, pH, viscosity, spreadability, foam height, irritation, and hedonic tests. Results: All formulations exhibited a white color, emulgel texture, and were odorless. Formula F1 had a pH of 7.3, F2 had 8.2, and F3 had 8.6. The highest viscosity was observed in F3 (4,200 cP), optimal spreadability in F2 and F3 (5.9 cm), and the highest foam height in F3 (4.6 cm). Only F1 approached the ideal skin pH range (4.5–6.5), although all formulations passed stability and organoleptic evaluations. Conclusion: Almond oil shows potential as an active ingredient in facial wash formulations. Formula F1 is considered the most suitable based on pH compatibility, while F3 excels in viscosity and foaming properties.